Stress testing with multi-faceted liquidity: The central bank collateral framework as a financial stability tool - Angelo Cuzzola; Claudio Barbieri; Ulrich Bindseil (European Central Bank (ECB), 2023)
The paper studies the central bank collateral framework and its impact on banks' liquidity under an adverse stress test scenario. We construct a stress test model that accounts for a granular and multi-faceted representation of the liquidity of marketable and non-marketable assets. In particular, the model analyses banks' strategic decisions to mobilise assets through four funding channels: unsecured loans, asset sales, private repurchase agreements, or Central Bank lending. We test three scenarios: the EBA regulatory stress test exercise, a shock to Russia and the Eastern European countries, and a shock to the Southern European countries. Results show that illiquidity can trigger insolvency and that liquidity adjustment can last significantly after the initial shock. We find evidence of a threshold in the benefits of expanding the collateral framework and highlight the heterogeneous effects across different jurisdictions and financial institutions. We find that bank equity losses are reduced in aggregate up to 17% at the tail of the loss distribution and on average by around 5% when financial institutions can rely on the collateral framework channel.
Keywords: C63; E52; G01; G28; 330; Central Bank Collateral Framework; Lender-Of-Last Resort; Asset liquidity; Collateral; Stress tes